Can behavioral finance models account for historical asset prices? - Rhys ap Gwilym (Cardiff University, Cardiff Business School, 2009)
I construct a behavioral model of asset pricing in which agents choose whether to base their expectations on chartist or fundamental forecasts. I simulate the model in order to test its efficacy in explaining the moments and time series properties of the FTSE All-Share index, and find that the model cannot be rejected as the data generating process.
Keywords: G12; D03; 330; Behavioral finance; Asset pricing; Finanzmarkt; Kapitalanlage; Verhaltensökonomik; Wirtschaftsprognose; Theorie